POTENTIAL OF INFORMAL BUSINESS NETWORKS IN service industry - O. Gabdrakhmanov (Вестник университета, 2017)
The article gives an overview of the potential of using informal business networks in the service industry. The author introduces the concept of informal business networks potential in the service industry, identifies its characteristics and some peculiarities of potential assessment.